Interactions among three species of cereal aphids simultaneously infesting wheat - Qureshi, Jawwad A.; Michaud, J. P. (My University, 2005)
Interactions among greenbug, Schizaphis graminum (Rondani), Russian wheat aphid, Diuraphis noxia (Mordvilko), and bird cherry-oat aphid Rhopalosiphum padi (L.) were examined on wheat plants (Triticum aestivum L., cultivar TAM 107). Nymphs were released on the plants as conspecific and heterospecific pairs of either first or fourth instars and evaluated for survival, developmental time, fecundity, intra-plant movement, and affinity to plant tissues. Survival from first instar to onset of reproduction averaged 90–100% across all pair combinations. Diuraphis noxia developed faster as conspecifics than in any heterospecific combination, and faster as conspecifics feeding on the same plant tissue than on different tissues. Fecundity of S. graminum was higher for conspecifics that developed on the same plant tissue than for those feeding separately. There was evidence of amensalism (one species was harmed while the other was unaffected) in that D. noxia experienced delayed development feeding in tandem with S. graminum, and reduced fecundity with both S. graminum and R. padi. Furthermore, S. graminum nymphs had reduced survival when their mothers matured on a same plant with R. padi. Both D. noxia and R. padi changed position on the plant more often when developing with S. graminum. Survival of second generation S. graminum nymphs was reduced when this species developed and reproduced in tandem with R. padi. Preferred feeding locations were S. graminum - primary leaf, D. noxia - tertiary leaf and R. padi - stem and these were not altered in any heterospecific combinations. Heterospecific aphids had no impact on fecundity or progeny survival in any species combination when fourth instars matured and reproduced on plants not previously exposed to aphid feeding, supporting the inference that systemic, aphid-induced changes in plant physiology mediated the effects observed when first instars developed and reproduced on the same plants.
Citation: Qureshi, J., & Michaud, J. (2005). Interactions among three species of cereal aphids simultaneously infesting wheat. Journal of Insect Science, 5(1). https://doi.org/10.1093/jis/5.1.13
Keywords: Amensalism; Schizaphis graminum; Development; Reproduction; Rhopalosiphum padi; Diuraphis noxia